2014
DOI: 10.1007/s13191-014-0361-3
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Prosthetic Reconstruction Using Polymethyl Methacrylate Implant: A Case Report

Abstract: Large cranial defects of complex geometric shapes are challenging to reconstruct. The cranial implants has to be fabricated prior to the cranioplastic surgery. The ideal material for cranial implant has to be inert, light weight, easy to fit and adaptable to the defect, offering the best aesthetic and functional results. Here is a clinical case report of a patient who was operated for osteomyelitis in the parieto-temporal region. The defect was reconstructed with heat cure polymethylmethacrylate (PMMA). Operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In one study, comparison was done in two patients for prosthesis construction directly on skull and printed directly using 3D technology. None of case reports/series reported any complications after the surgery and reported satisfactory/ improved/good/excellent aesthesis [29][30][31][32][33][34][35][36] (►Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, comparison was done in two patients for prosthesis construction directly on skull and printed directly using 3D technology. None of case reports/series reported any complications after the surgery and reported satisfactory/ improved/good/excellent aesthesis [29][30][31][32][33][34][35][36] (►Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 3D-printed PMMA or titanium prostheses were reported to have favorable outcomes. PMMA acrylic prostheses are more susceptible to infection [ 12 ] and tissue necrosis, which not only necessitates prostheses removal [ 13 ] but also jeopardizes the soft tissue over the defect, making further reconstructions more challenging [ 4 ]. Jaberi et al reconstructed 70 patients with PMMA custom-made implants and reported a 24% complication rate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether prefabricated or custom-made, alloplastic materials are mainly made from titanium or polymathic methacrylate (PMMA) [ 3 ]. PMMA is economically affordable [ 3 , 4 ]; however, it is not as strong as titanium [ 5 ]. Moreover, PMMA prostheses are more prone to infection, local irritation, foreign body reaction, and thermal damage during polymerization in the case being used as a cement for prosthesis adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Each material poses their own advantages and disadvantages 3 . Cranial Implants made from PMMA are stable, biocompatible, chemically inert, nonconductive, radioluent, and inexpensive and can be easily placed and modified [4][5][6] . Thus it accomplishes the requirements but durability and the reaction of the PMMA implant is questionable and technique sensitive .…”
Section: Introductionmentioning
confidence: 99%